Selective Hedging of Foreign Exchange Risk: New Evidence from French Non-Financial Firms - Albouy, Michel; Dupuy, Philippe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
We provide survey evidence on the use of derivatives for the management of foreign exchange risk among French non-financial firms. We focus particularly on the way firms might alter the size and the timing of the hedges, a practice called selective hedging. We rely on observations gathered between 2010 and 2015 via e-mail surveys and one-on-one interviews. The results show that French corporations are hedging more systematically than their foreign counterparts. Together, we observe that highly indebted and smaller firms tend to be more selective. We relate our findings to cultural differences and communication issues.